COMPARATIVE ANALYSIS OF EXACT AND ITERATIVE METHODS FOR SOLVIN SLAES - Varmashin, Evgeni; Vasileva, Anna (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2018)
The numerical solution of systems of linear algebraic equations (hereinafter SLAE) is one of the most frequently encountered problems in scientific and technical research, mathematical physics (numerical solution of differential and integral equations), economics, statistics. According to modern literature, about 75% of all computational problems lead to the solution of systems of linear algebraic equations. And, accordingly, the need to choose the method of solving SLAE, giving, with the use of computer technology, an effective result is actualized. This article compares the different methods for solving SLAE